Manipulation techniques aiming at discrediting the Church among soldiers of the Polish People’s Army during John Paul’s II second pilgrimage to Poland - ORŁOWSKI, Paweł (Historia i Świat, 2023)
The aim of the following article is to present how the Armed Forces of the Polish People's Republic reacted to the second pilgrimage of John Paul II to Poland. It outlines multiple processes, mainly of social origin, which occurred during the preparations for the visit, its course and after its completion. Moreover, the author depicts political and cultural circumstances in which soldiers and conscripts had to serve. At the same time, numerous manipulation techniques that were used to discredit the Catholic Church have been included.